Experimental investigation of a novel solar thermal polygeneration plant in United Arab Emirates. (June 2016) - Mohan, Gowtham; Uday Kumar, N.T.; Pokhrel, Manoj Kumar; Martin, Andrew
Abstract: The demands for space air conditioning and clean drinking water are relatively high in Middle East North African (MENA) countries. A sustainable and innovative approach to meet these demands along with the production of domestic hot water is experimentally investigated in this paper. A novel solar thermal poly-generation (STP) pilot plant is designed and developed for production of chilled water for air conditioning using absorption chiller, clean drinking water with membrane distillation units and domestic hot water by heat recovery. The STP system is developed with a flexibility to operate in four different modes: (i) solar cooling mode (ii) cogeneration of drinking water and domestic hot water (iii) cogeneration of cooling and desalination (iv) trigeneration. Operational flexibility allows consumers to utilize the available energy based on seasonal requirements. Performance of STP system is analyzed during summer months in RAKRIC research facility. Energy flows in STP pilot plant during peak load operations are analyzed for all four modes. STP system with trigeneration mode utilizes 23% more useful energy compared to solar cooling mode, which improves overall efficiency of the plant. Economic benefits of STP with trigeneration mode are evaluated with fuel cost inflation rate of 10%. STP plant has potential payback period of 9.08 years and net cumulative savings of 454, 000 based on economic evaluation. Highlights: Experimental investigation of solar thermal polygeneration system is conducted. Membrane distillation units are integrated with absorption chiller for achieve polygeneration. Developed with flexibility to operate in four different modes.